A new Cannabis genome assembly associates elevated cannabidiol (CBD) with hemp introgressed into marijuana. Issue 4 (28th February 2021) - Grassa, Christopher J.; Weiblen, George D.; Wenger, Jonathan P.; Dabney, Clemon; Poplawski, Shane G.; Timothy Motley, S.; Michael, Todd P.; Schwartz, C. J.
Summary: Demand for cannabidiol (CBD), the predominant cannabinoid in hemp ( Cannabis sativa ), has favored cultivars producing unprecedented quantities of CBD. We investigated the ancestry of a new cultivar and cannabinoid synthase genes in relation to cannabinoid inheritance. A nanopore‐based assembly anchored to a high‐resolution linkage map provided a chromosome‐resolved genome for CBDRx, a potent CBD‐type cultivar. We measured cannabinoid synthase expression by cDNA sequencing and conducted a population genetic analysis of diverse Cannabis accessions. Quantitative trait locus mapping of cannabinoids in a hemp × marijuana segregating population was also performed. Cannabinoid synthase paralogs are arranged in tandem arrays embedded in long terminal repeat retrotransposons on chromosome 7. Although CBDRx is predominantly of marijuana ancestry, the genome has cannabidiolic acid synthase ( CBDAS ) introgressed from hemp and lacks a complete sequence for tetrahydrocannabinolic acid synthase ( THCAS ). Three additional genomes, including one with complete THCAS, confirmed this genomic structure. Only cannabidiolic acid synthase ( CBDAS ) was expressed in CBD‐type Cannabis, while both CBDAS and THCAS were expressed in a cultivar with an intermediate tetrahydrocannabinol (THC) : CBD ratio. Although variation among cannabinoid synthase loci might affect the THC : CBD ratio, variability among cultivars in overall cannabinoid content (potency) was also associated with other chromosomes.